Actually-Existing Success: Economics, Aesthetics, and the Specificity of (Still-)Socialist Urbanism - Murawski, Michał (. Comparative studies in society and history. - Cambridge : Cambridge Univ. Press, 1958-. - Online-Ressource. - ISSN 1475-2999 60, 2018)
A quarter century following the collapse of the Soviet Union and the people's democracies, many of the dwellings, utilities, and public spaces built by these regimes continue to be cherished by their inhabitants and users. This has only increased as post-socialist urban landscapes undergo an ever-intensifying process of neoliberal “re-privatization,” de-planning, and spatial as well as economic stratification. Scholars, however, continue to produce accounts emphasizing how socialist cities and buildings, as well as the audacious social goals built into them, failed. This article provides a critical overview of recent literature on built socialism and identifies a tension between two parallel ethnographic and historical narratives. One argues that built socialism failed, because it was too obsessed with the economy and industry and neglected every other aspect of social life. The other pins the blame for failure on built socialism's alleged fixation with aesthetic or discursive realms and its corresponding neglect of the economy. The article closes by suggesting pathways for comparative scholarship that consider built socialism in terms of not only collapse and disintegration, but also success and endurance; not simply of either economy or aesthetics, but also of their reciprocal inter-determination and co-dependence. We must look beyond the lens of imported theories and consider “vernacular” or “emic” concepts rooted in the specificities and singularities of the socialist city itself.